1958
DOI: 10.1107/s0365110x58000529
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco mosaic virus: application of the method of isomorphous replacement to the determination of the helical parameters and radial density distribution

Abstract: It is known that in tobacco mosaic virus (TMV) structurally equivalent protein sub-units lie in helical array about the long axis of the rod-shaped particle. It has not, however, proved possible to make a reliable determination of the helical parameters by the usual methods of direct measurement on X-ray fibre diagrams.A quantitative comparison has now been made of the equatorial intensities in fibre diagrams of TMV and of a mercury-substituted TMV, TMV-Hg. This has led to the determination, first of the radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1965
1965
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(30 citation statements)
references
References 9 publications
(14 reference statements)
1
29
0
Order By: Relevance
“…The positions of the remaining equatorial peaks in Fig. 1 A are consistent (26) with continuous diffraction from a filament approximating a solid cylinder of diameter 55 Å. They might also be explained by arrays of regularly-spaced fibrils of any structure, but this explanation is inconsistent with the complete absence of low-angle diffraction from some fibers.…”
Section: Resultsmentioning
confidence: 54%
“…The positions of the remaining equatorial peaks in Fig. 1 A are consistent (26) with continuous diffraction from a filament approximating a solid cylinder of diameter 55 Å. They might also be explained by arrays of regularly-spaced fibrils of any structure, but this explanation is inconsistent with the complete absence of low-angle diffraction from some fibers.…”
Section: Resultsmentioning
confidence: 54%
“…3. This is a reasonable value when compared with that estimated on the basis of the radial electron density distribution for tobacco mosaic virus (Franklin & Holmes, 1958). It can be seen from that the effect of the hole is to displace the first zero position of the transform and this accounts for the observed (1,0) reflection.…”
Section: X-ray Diffractionsupporting
confidence: 52%
“…2A) at resolutions between 65 Å and 22 Å. The origin peak (data inside the equatorial node at 110 Å) was calculated from a solid cylinder, scaled in amplitude to the low-angle amplitudes and radially to the first node position (26,34). The positions of the peaks in the distribution are probably influenced by series termination error; they remain even when very large temperature factors are imposed upon the equatorial amplitudes, but their positions depend on the resolution of the input data.…”
Section: Resultsmentioning
confidence: 99%
“…In consequence, diffracted amplitude maxima that are sufficiently close together must have alternating signs. The minimum-wavelength principle was used by Caspar (13) in TMV studies, and the signs determined for TMV were subsequently shown by isomorphous replacement to be correct (26,48).…”
Section: Methodsmentioning
confidence: 99%